Development of Low Cost Coconut Water Vinegar Making Process and Evaluation of “Generator Process” to Accelerate the Acetification - Gunathilake, K. D. P. P.; Fernando, J. A. K. M.; Jayawickrama, D. S. (International Coconut Community Journal, 2011)
Attempts were made to develop an appropriate low cost vinegar making technique and evaluate the physico-chemical, microbial and sensory qualities of the product. Coconut water was adjusted to four different levels of sugar levels (12%, 15%, 17%, and 20%) and pasteurized sweetened coconut water was allowed for alcoholic fermentation for one week by addition of baker’s yeast and then for acetic fermentation by addition of raw vinegar at 10%. Changes in alcohol %, titratable acidity, pH and yeast and mold count were determined periodically. Best treatment was selected for evaluation of the vinegar generator. Vinegar generator consists of a feeding device, an acetifier and a receiving trough. The acetifier was filled up with maize cobs soaked with mother vinegar. The maximum alcohol content was observed in 17° TSS coconut water sample on 5th day (9%) of alcohol fermentation and the same sample achieved the highest acetic acid level during acetic fermentation period. Results indicated that vinegar generator accelerates the conversion of alcohol to acetic acid within 5 cycles or runs. It takes about 32 hours to obtain the 4% acetic level. Sensory evaluation was done to determine the acceptability of product using 30 untrained panelists. Sensory evaluation revealed that coconut toddy vinegar and coconut water vinegar were highly acceptable for aroma, taste, color, appearance and overall acceptability. Mature coconut water can be used to produce vinegar with the aid of vinegar generator for accelerating the production process.